Effect of Concentration on Properties of Vacuum Coagulated Natural Rubber Latex. Issue 2 (February 2019) - He, Shuang; Liao, Shuangquan; Zhao, Yanfang; Liao, Xiaoxue
Abstract: Vacuum treatment was used to coagulate natural latex, the effects of latex concentration on physical and chemical properties, mechanical properties, molecular weight and crosslink density of vacuum coagulated natural rubber latex (NRL) were investigated. Studies have shown that with the increase of latex coagulated concentration, the nitrogen content of natural rubber (NR) increases and the ash content decreased. In the range of coagulated concentration studied, the plasticity initial value ( P0 ) and plastic retention rate (PRI) ratio of low concentration solidified raw rubber were higher than high concentration of NR. The tensile strength of NR decreased with the increase of solidification concentration. The molecular weight have shown a bimodal distribution, and the number average molecular weight (Mn), weight average molecular weight (Mw), and z average molecular weight (Mz) increased with the solidification concentration of latex, and the dispersion coefficient decreased. With the increase of solidification concentration, the crosslink density of NR decreased first and then increased. The relative molecular mass (Mc) of the rubber cross-linking point increased first and then decreased with the increase of solidification concentration.